An investigation teachers' instructional decisions on the development of learners' entrepreneurial skills in agricultural sciences in the Limpopo Province, South Africa : a case of the Sekhukhune District - Masha, Mmapake Florence (My University, 2021)
The development of learners’ entrepreneurial skills in Agricultural Sciences remains as one of the crucial aspects in the midst of the high unemployment rate in South Africa. Development of these skills depends on the capacity of teachers’ instructional decisions. These skills play a significant role in the agricultural sector as this sector experiences changes in the production and marketing of agricultural products. These significant changes demand relevant skills, such as negotiation skills, critical thinking skills and creativity skills, in order to support these changes and also for school leavers to remain relevant in the 21st century. Therefore, it is against this background that the study sought to investigate teachers’ instructional decisions on the development of learners’ entrepreneurial skills in an Agricultural Sciences classroom. The social reconstructionism theory was used as a framework to guide how teaching and learning should be structured in order to develop agricultural entrepreneurial skills. The study was submersed in the exploratory mixed method approach. Purposive and systematic sampling were used to select 4 teachers and 100 Grade 12 Agricultural Sciences learners from 4 local secondary schools in the Sekhukhune District of Limpopo, from whom the data were collected through the use of observational inventory and questionnaires. Interpretative analysis and a multinomial logistic regression model were used to analyse the collected data. The study found that Agricultural Sciences lessons were dominated by traditional methods for both teaching and assessment because teaching is geared towards passing control tests and examinations rather than towards the development of skills. Furthermore, a lack of professional knowledge was also visible, where lessons were not properly planned and the teachers’ inability to relate the lesson to reality was evident. It was also observed from the results of the multinomial logistic regression that other factors that influence the development of agricultural entrepreneurial skills include, among others, the type of questions asked, the learning environment and the number of practical lessons. The study further found that 68% of learners prefers to learn through interact methods other than the traditional methods. The results further indicated that learners have positive attitudes towards learning agricultural entrepreneurship and they also use iii some this knowledge in their daily activities. Therefore, as a result of this study, the researcher recommends that the Department of Basic Education, in conjunction with institutions of higher learning, provide regular workshops or training opportunities for Agricultural Sciences teachers so that they become relevant practitioners of developing learners’ agricultural entrepreneurial skills. The workshops should focus mainly on planning a lesson for a vocational subject like Agricultural Sciences, and emphasis should be placed on the type of resources relevant to the teaching of Agricultural Sciences.
Thesis (Ph. D. Education (Science Education)) -- University of Limpopo, 2021
Keywords: Agricultural sciences; Entrepreneurial skills; Teaching methods; Teachers and learners; Agriculture -- Study and teaching; Education, Cooperative; Fieldwork (Educational method); Entrepreneurship